Genomatica: an integrated data management and analysis tool for genome sequencing projects - Sato, Kenji; Miyajima, Nobuyuki; Furukawa, Tetsuya; Murakami, Yasufumi; Ogasawara, Naoki; Mori, Hirotada; Kuhara, Satoru; Akiyama, Yutaka (Genome Informatics, 1993)
Genomatica is an integrated software tool designed for helping systematic management of a large number of DNA sequence fragments obtained through a genome sequencing project. Its graphic user-interface also allows users to look, with any magnifying factor, into any position of the specified chromosome and to browse various kinds of collected information altogether (including: DNA sequence itself, related gene descriptions, bibliographic references, corresponding GenBank entries, confirmed or putative coding regions, results from homology analysis for the expected protein, RNA genes, clone information, enzyme restriction maps, comments from administrator, private memorandums by user). We are planning to use Genomatica in E. coli (local data compilation mainly managed by Mori), B. subtilis (by Ogasawara), and S. cerevisiae (by Murakami) genome sequencing projects. The Genomatica project was started on 1992 as one of the advanced genome database projects sponsored by Human Genome Center, University of Tokyo. In June 1993, ver. 2.0 which was fully re-designed with NCBI vibrant library was released. Further augmented version Genomatica 2.1 (with several sequence analysis functions and network communication modules) will be released on Nov. 1993 and will be distributed through anonymous ftp services. The Genomatica system is currently available for X11 window system on Unix workstations, but Macintosh and IBM-PC versions will be also announced soon.